Scientific production and international insertion of the journal Scire in the 2006-2014 period - Tannuri de Oliveira, Ely Francina [UNESP]; Alves, Bruno Henrique [UNESP]; Prado, Marcos Rodrigues do [UNESP]; Pavanelli, Maria Aparecida [UNESP] (Univ Zaragoza, 2017)
A bibliometric analysis of the scientific production of the journal Scire: Representacion y organizacion del Conocimiento in the 2006-2014 period is offered, in order to show its internationalization. Specifically, the study aims to highlight institutions with higher productivity in their countries, as well as to examine institutional co-authorships, highlighting the international co-authorships and the most important themes. As total of 73 institutions were investigated, with 23 publishing at least two investigations. A network of institutional collaboration was created, a list of themes worked by the various collaborating institutions was developed, and the institutions were grouped according to Dahlberg's categories. The institutions and themes were grouped into clusters according to thematic similarity and presented through a dendrogram. As a conclusion, it was observed that the internationalization of the journal Scire is a trend, although fragile, especially in relation to Latin America.
Keywords: Knowledge organization; Scientific production; Internationalization; Scire; Institutional co-authorship; Classification System for Knowledge Organization Literature Latin America